Building a Raspberry Pi based air quality measuring device for chemistry education - Swanljung, Maria (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
This article outlines the building and use of a Raspberry Pi based measuring device capable of detecting air quality. The device can be used in chemistry teaching as a tool to demonstrate air composition or used in air chemistry laboratory experiments. The project is supported by theories of project-based learning, laboratory work and implementation of technology into chemistry. This article also provides a lesson plan using the device.